Effects of the Application of Virtual Reality to Experiential Education on Self-Efficacy and Learning Motivation of Social Workers - Hsiao, Suh Chen (Frontiers in Psychology, 2021)
To enhance human resources required for national development to cope with the change, countries in the world have positively invested in education, as national education in the future has to cultivate new-generation citizens with new traits and abilities to cope with possible impacts and challenges in the new century. For this reason, the education reform wave sweeps many countries. The experiential learning model in experiential education nowadays also leads profit and non-profit organizations in business community, education, and social worker groups to the alternative education trend. Various experiential learning curricula are therefore spread. Taking social workers in southern Taiwan as the research objects, total 227 social workers are preceded the 15-week (3 hours per week for total 45 hours) experimental research with the application of virtual reality to experiential education. The research results summarize that 1.experiential education with virtual reality would affect self-efficacy, 2.experiential education with virtual reality would affect learning motivation, and 3.self-efficacy reveals remarkably positive effects on learning motivation. According to the results to proposed discussions, it is expected to increase the interaction among social workers through the learning activity and internalize the experience in the practical learning process of communication, problem solving, and extrinsic interaction for the application to the work in order to achieve the better life.